2018
DOI: 10.11606/s1518-8787.2018052000184
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Diet Quality Index Adapted for Pregnant Women

Abstract: OBJECTIVE:To develop a Diet Quality Index Adapted for Pregnant Women (IQDAG) and to evaluate its relation with the characteristics of women treated at the Brazilian Unified Health System.METHODS:The data on food intake come from a cross-sectional study carried out with 785 adult pregnant women in the city of Ribeirão Preto, state of São Paulo, Brazil, between 2011 and 2012. The index was based on the recommendations of the Brazilian Ministry of Health, previous national dietary indexes, and the new Dietary Gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 27 publications
0
29
1
19
Order By: Relevance
“…The mean total HEI score (52.76–56.10) for pregnant women in this study was substantially lower than those reported in Western countries (62.9–70.2) [16,17,44,45] but almost parallel to those in other Asian countries, such as Singapore (52.4) [13] and Indonesia (58.9) [15]. Cross-study variations in HEI scores could be explained by the differences in study design, measurement of dietary intake (e.g., diet recall, diet history, food frequency questionnaire), socio-demographic background (e.g., age, ethnicity, and nutritional knowledge) and food environment (e.g., accessibility to fast food, convenience store and food court setting).…”
Section: Discussioncontrasting
confidence: 79%
“…The mean total HEI score (52.76–56.10) for pregnant women in this study was substantially lower than those reported in Western countries (62.9–70.2) [16,17,44,45] but almost parallel to those in other Asian countries, such as Singapore (52.4) [13] and Indonesia (58.9) [15]. Cross-study variations in HEI scores could be explained by the differences in study design, measurement of dietary intake (e.g., diet recall, diet history, food frequency questionnaire), socio-demographic background (e.g., age, ethnicity, and nutritional knowledge) and food environment (e.g., accessibility to fast food, convenience store and food court setting).…”
Section: Discussioncontrasting
confidence: 79%
“…Está bem estabelecida a associação entre fatores nutricionais e o desenvolvimento de patologias ou complicações na gestação (Gomes et al, 2019). Tendo em vista a importância de uma ingestão alimentar adequada, a avaliação do consumo alimentar de gestantes é necessária para identificar distúrbios nutricionais e metabólicos (Zuccolotto et al, 2019 (Crivellenti et al, 2018).…”
Section: Introductionunclassified
“…Como componente moderador da dieta, Crivellenti et al (2018), incorporou no IQDAG a porcentagem calórica proveniente de alimentos ultraprocessados como bebidas açucaradas, biscoitos, pães industrializados, macarrão instantâneo, sorvetes, chocolates, enlatados, embutidos e produtos congelados prontos para aquecimento, conforme recomendações do guia alimentar para a população brasileira.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Dietary indices are tools that assess overall diet quality and are based on theoretical assumptions about the effect of food and nutrients on the health of individuals (10). The Diet Quality Index Adapted for Pregnant Women (Índice de Qualidade da Dieta Adaptado para Gestantes -IQDAG) was developed for Brazilian pregnant women and is unprecedented in using the percentage of energy from ultra-processed foods as its moderator component (11).…”
Section: Introductionmentioning
confidence: 99%